2015
DOI: 10.1140/epjd/e2015-50845-9
|View full text |Cite
|
Sign up to set email alerts
|

A variational approach to repulsively interacting three-fermion systems in a one-dimensional harmonic trap

Abstract: We study a three-body system with zero-range interactions in a one-dimensional harmonic trap. The system consists of two spin-polarized fermions and a third particle which is distinct from two others (2+1 system). First we assume that the particles have equal masses. For this case the system in the strongly and weakly interacting limits can be accurately described using wave function factorized in hypercylindrical coordinates. Inspired by this result we propose an interpolation ansatz for the wave function for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 71 publications
3
30
0
Order By: Relevance
“…It is worth noting that for N 1 =  and N 2 =  our results obtained in the strong interaction limit are consistent with the density profiles obtained in [39] where a variational approach was used for this three-body problem.…”
Section: Properties Of the Ground Statesupporting
confidence: 88%
See 1 more Smart Citation
“…It is worth noting that for N 1 =  and N 2 =  our results obtained in the strong interaction limit are consistent with the density profiles obtained in [39] where a variational approach was used for this three-body problem.…”
Section: Properties Of the Ground Statesupporting
confidence: 88%
“…For large but finite repulsions the spectrum of the Hamiltonian is not degenerate but it factorizes into distant manifolds of quasi-degenerate eigenstates. The mechanism that lifts the degeneracy and its experimental consequenceshas been broadly discussed recently [39,52]. It is worth noting that the case of…”
Section: Spectrum Of the Hamiltonianmentioning
confidence: 99%
“…In this way we were able to perform analysis of many different properties of the system, regardless of the excitations of the centre of mass. The procedure has been applied to systems with different number of fermions and different mass ratio generalizing previous results [11,15]. To investigate the properties of a system confined in a harmonic trap we have shown that eigenstates are characterized by specific invariants that can be straightforwardly calculated from the observable available in the experiment.…”
Section: Discussionmentioning
confidence: 92%
“…[50] can lead to errors already at the level of four particles [43]. In our recent work on few-fermion physics, we have considered three-body problems both for two- [53] three-component systems [54]. A new variational approach was introduced in Ref.…”
Section: Fermionic Systemsmentioning
confidence: 99%